2023
DOI: 10.12688/wellcomeopenres.18937.2
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the transmembrane protein 2 (TMEM2) ectodomain and its apparent lack of hyaluronidase activity

Abstract: Background: Hyaluronic acid (HA) is a major polysaccharide component of the extracellular matrix. HA has essential functions in tissue architecture and the regulation of cell behaviour. HA turnover needs to be finely balanced. Increased HA degradation is associated with cancer, inflammation, and other pathological situations. Transmembrane protein 2 (TMEM2) is a cell surface protein that has been reported to degrade HA into ~5 kDa fragments and play an essential role in systemic HA turnover. Methods: We produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…S4 ) (p.His552 in Hs TMEM2, Fig. 4 a; Protein Data Bank (PDB): 8C6I (Niu et al 2023 )) reported to form a nickel-finger binding site, which might mediate catalytic functions in TMEM2. Disruption of this site in PKHD1L1 and TMEM2 might impair cation binding (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S4 ) (p.His552 in Hs TMEM2, Fig. 4 a; Protein Data Bank (PDB): 8C6I (Niu et al 2023 )) reported to form a nickel-finger binding site, which might mediate catalytic functions in TMEM2. Disruption of this site in PKHD1L1 and TMEM2 might impair cation binding (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S3 for full PKHD1L1 sequence alignment). Residue numbering for TMEM2 as in PDB: 8C6I (Niu et al 2023 ), while residue numbering for Hs PKHD1L1 as in NCBI accession code NP_803875.2 with the signal peptide included (Supplementary Table S1 , 26 residues are suggested according to protein sequence alignment, see Methods). Green triangles point to the location of the Hs p.(His2479Gln) variant, orange circles ( left ) indicate 100% amino acid sequence identity for this PKHD1L1 fragment between the Hs , Pt , and Mm2 species (See supplementary Table S1 for details about the selected orthologs).…”
Section: Resultsmentioning
confidence: 99%
“…S4) (p.His552 in Hs TMEM2, Fig. 4a; Protein Data Bank (PDB): 8C6I (Niu et al 2023)) reported to form a nickel-finger binding site, which might mediate catalytic functions in TMEM2. Disruption of this site in PKHD1L1 and TMEM2 might impair cation binding (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TableS1for details of the selected species, Supplementary Fig.S4for sequence alignment of this specific fragment, and Supplementary Fig.S3for full PKHDL1 sequence alignment). Residue numbering for TMEM2 as in PDB: 8C6I(Niu et al 2023), while residue numbering for Hs PKHD1L1 as in NCBI accession code NP_803875.2 with the signal peptide included (Supplementary TableS1, 26 residues are suggested according to protein sequence alignment, see Methods). Green triangles point to the location of the Hs p.(His2479Gln) variant, orange circles (left) indicate 100% amino acid sequence identity for this PKHD1L1 fragment between the Hs, Pt, and Mm2 species (See supplementary Table…”
mentioning
confidence: 99%
“…The crystal structure of the TMEM2 ectodomain. (a) Overview of the structure (PDB: 8C6I) with domains colour‐coded and labelled (Niu et al., 2023). Fibrocystin is predicted to have two G8 domains, each followed by parallel β‐helical repeats, possibly folding into a similar conformation as those of TMEM2.…”
Section: Fibrocystin Structurementioning
confidence: 99%